Sleep Calls and Emotional Intimacy in Non-Long-Distance Romantic Relationships: A Qualitative Exploration of Virtual Communication Practices - Timmy Ardian Roring; Jefri Setyawan (FAKULTAS DAKWAH UIN SALATIGA, 2025)
In the context of modern romantic relationships in Indonesia, digital communication has facilitated the maintenance of intimacy and commitment beyond face-to-face interactions. One such practice, sleep calls, has gained prominence even among non-long-distance couples, raising questions about its role in emotional bonding and relationship dynamics. This study investigates how sleep calls function within non-long-distance romantic relationships, focusing on their potential to strengthen intimacy, foster self-disclosure, and provide social support. Through qualitative data from in-depth interviews with two couples, this research examines how sleep calls are perceived and utilized to enhance emotional closeness, while also exploring potential drawbacks, such as the impact on sleep quality. Findings suggest that sleep calls serve as a unique form of virtual intimacy, allowing couples to nurture emotional connections and demonstrate commitment, but also posing challenges to physical well-being. By positioning this study within the broader context of virtual communication in contemporary relationships, we argue that while sleep calls can significantly deepen emotional bonds, their long-term effects on relationship satisfaction and individual health remain an important area for future exploration.